Quality of life in stiff-person syndrome. - Gerschlager, W; Schrag, A; Brown, P (2002)
Stiff person syndrome (SPS) is a rare, chronic disorder characterized by painful spasm and stiffness. We investigated the quality of life (QoL) in SPS patients, and identified factors associated with impairment in patients' QoL. Twenty-four SPS patients (10 men, 14 women; mean age +/- S.D., 52.6 +/- 9.5 years) completed the medical outcomes study Short Form health survey (SF-36), the Beck Depression Inventory (BDI), and a questionnaire asking for sociodemographic and clinical details. Extent of the disease was assessed using a distribution of stiffness score. SPS patients showed markedly reduced mean scores for all dimensions of the SF-36 when compared to norms from the general population of the United Kingdom. QoL scores showed a strong correlation with the extent of the disease. Depression was a common finding; 14 of 24 patients had depressive symptoms as evidenced by the BDI. There was a significant and strong correlation between the BDI score and several SF-36 subscores. This is the first study to address QoL in patients with SPS. We have shown that SPS has a significant impact on patients' reported QoL. The association between depression and QoL highlights the importance of recognizing and treating depression in SPS.